Implementation of Industrial Relations Dispute Settlement Between Workers and Employers Through Mediation at the Gresik Regency Manpower Office in 2021 – 2023 - Muhammad Firdaus Iqbal; Mahendra Wardhana (Universitas Negeri Surabaya, 2024)
In Article 1 paragraph (11) of Law Number 2 of 2004 concerning Industrial Relations Dispute Settlement, Industrial Relations Mediation hereinafter referred to as mediation is the settlement of disputes over rights, interest disputes, employment termination disputes, and disputes between labor unions only within one company through deliberations mediated by one or more neutral mediators. According to this article, mediation at the Labor Office of Gresik Regency is led by one mediator totaling 6 industrial relations mediators. This study was conducted to find out first, how is the implementation of industrial relations dispute settlement between workers and employers through mediation at the Labor Office of Gresik Regency in 2021-2023? Second, what are the obstacles faced by industrial relations mediators in conducting mediation at the Labor Office of Gresik Regency in 2021-2023? This research uses empirical legal research methods with a socio-legal approach which is an approach from the perspective of society with data collection methods through interviews with mediators and workers, observations, and documentation. The research results indicate that: First, the implementation of mediation at the Labor Office of Gresik Regency has been carried out well with a success rate in mediation of over 50%, both through collective agreements and recommendations. Second, the obstacles encountered in the mediation process are due to various factors, namely the employer factor who is often late or absent from mediation sessions, the worker factor of lack of evidence and understanding of applicable regulations, and the mediator factor of insufficient number of mediators and facilities.